Bacillus velezensis LT1: a potential biocontrol agent for southern blight on Coptis chinensis - Tang, Tao; Wang, Fanfan; Huang, Houyun; Guo, Jie; Guo, Xiaoliang; Duan, Yuanyuan; Wang, Xiaoyue; Wang, Qingfang; You, Jingmao (Frontiers in Microbiology, 2024)
The management of the southern blight in Coptis chinensis caused by Sclerotium rolfsii remains a significant challenge in production. Overuse of fungicides has led to excessive pesticide residues and increasing resistance to these chemicals, making it difficult to prevent the spread of S. rolfsii.In this study, we isolated Bacillus velezensis LT1 from the rhizosphere of severely affected C.chinensis and assessed its biocontrol potential against S. rolfsii LC1 using a confrontation assay. We also identified the lipopeptide antimicrobial compounds in the fermentation liquid of B. velezensis LT1 using MALDI-TOF-MS and observed the effect of B. velezensis LT1 on the mycelial [在此处键入] morphology of S. rolfsii LC1 using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The confrontational assay revealed that B. velezensis LT1 has significant antifungal potential against S. rolfsii LC1, with a 78.41% inhibition efficiency. Analysis of bacterial lipopeptide antimicrobial compounds in the fermentation liquid of B. velezensis LT1 by MALDI-TOF-MS revealed the presence of bacillomycin, surfactin, iturin, and fengycin, which have been previously reported to have antifungal activity. The mycelial and cell structures of S. rolfsii LC1 were significantly abnormal under pressure from B. velezensis LT1, as observed through SEM and TEM. This study confirms the potential of B. velezensis LT1 as an effective biocontrol agent against S. rolfsii LC1 and opens up avenues for further exploration of its genetic potential. It is crucial to find alternative, sustainable approaches to control plant diseases, and this study offers a promising step in that direction.